2021
DOI: 10.1029/2021gl096341
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of Ocean Chaotic Intrinsic Variability on Bottom Pressure and Implications for Data and Model Analyses

Abstract: Ocean bottom pressure (p b ) variability reflects changes in mass of the water column arising from freshwater fluxes at the ocean boundaries and horizontal mass redistribution by the ocean circulation (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Our findings show the notable large-scale impacts on the p b field of random intrinsic processes. The global-scale p i b signature identified in this work is also reflected in the substantial p i b variations found in relatively quiet eddy areas, such as the eastern Atlantic Ocean (16). Our analyses indicate that such global-scale p i b variability can amount to at least half of p f b variability in those regions and can thus be important for understanding p b variability in extensive ocean regions.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings show the notable large-scale impacts on the p b field of random intrinsic processes. The global-scale p i b signature identified in this work is also reflected in the substantial p i b variations found in relatively quiet eddy areas, such as the eastern Atlantic Ocean (16). Our analyses indicate that such global-scale p i b variability can amount to at least half of p f b variability in those regions and can thus be important for understanding p b variability in extensive ocean regions.…”
Section: Discussionsupporting
confidence: 63%
“…Nonlinear mesoscale (or smaller scale) turbulence is the best-known example of these intrinsic processes, which generate random pbi variations at spatial scales of order 100 km and time scales of weeks to months. However, recent modeling studies have shown that pbi variations could be as important as those of pbf at scales of order 1000 km ( 13 , 16 ). In the intra-annual frequency band, pbi can actually be larger than pbf in almost a quarter of the ocean area ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…OBP variations at mid-high latitudes on sub-seasonal to interannual timescales are mainly affected by wind forcing (Niu et al, 2022), the hydrological cycle (Chambers et al, 2004), atmospheric pressure (Cheng et al, 2021) and baroclinic processes (Vinogradova et al, 2007). In addition to this forced variability, the OBP may have chaotic intrinsic variability in eddy-active regions, arising from non-linear ocean processes () Zhao et al, 2021. The importance of this intrinsic variability on GRACE interpretations at different spatiotemporal scales is only now starting to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed a good match between the GRACE estimates, large-scale OBP and global mean sea level from altimetry (Chambers et al, 2004), however subsequent studies showed that the link between sea level and OBP derived from GRACE is broken by baroclinic processes, depending on spatial and temporal scales as well as on the geographic region (Ponte et al, 2007;Bingham and Hughes, 2008;Chambers and Schroter, 2011;Zhang et al, 2018, Chen et al, 2021. Recent research also indicates that the comparison between GRACE and in-situ OBP measurements is often not satisfactory not only because of GRACE's low spatial and temporal resolution, but also due to a chaotic intrinsic variability resulting from the non-linear interactions between oceanic and atmospheric processes (Zhao et al, 2021).…”
Section: Proxies For Ocean Loadingmentioning
confidence: 99%
“…Due to the chaotic nature of the ocean (Poincaré, 1890;Lorenz, 1963), trajectories of eddying numerical simulations are sensitive to initial condition uncertainties (Sérazin et al, 2017;Leroux et al, 2018;Jamet et al, 2019;Zhao et al, 2021;. This allows us to develop an ensemble of ocean simulations, differing only in small ways in their initial conditions; i.e.…”
Section: Eddy Definitionmentioning
confidence: 99%